National culture: The missing country-level determinant of corporate governance - Griffin, Dale; Guedhami, Omrane; Kwok, Chuck C Y; Li, Kai; Shao, Liang (Journal of International Business Studies, 2017)
It is well known that firm-level corporate governance practices vary mainly between rather than within countries, but country-level factors such as legal and financial institutions explain less than 50% of this cross-country variation. In this article we show that two dimensions of national culture – individualism and uncertainty avoidance – capture about 90% of the country fixed effects and outperform the country-level explanatory variables used in prior literature. We argue that culture works through a tradeoff between managerial expertise and certainty of control, a tradeoff largely overlooked by prior literature, that captures a country’s preference for the Anglo-Saxon approach versus the direct control approach for governance. Consistent with this argument, we find that the effect of culture on corporate governance varies across firms with different needs for managerial expertise and certainty of control. We also find that culture interacts with other factors to determine firm-level governance.